Behavioral approach to food consumption and waste production: A quasi-experimental study - Yazdankhah, Zahra (J Educ Health Promot, 2020)
BACKGROUND: Approximately one third of the food produced in the world for human consumption was wasted. OBJECTIVES: This study aimed to determine the effect of intervention on behavior of food consumption and waste production in the restaurants of Shahid Beheshti University of Medical Sciences. MATERIALS AND METHODS: In this quasi-experimental study, 233 students of public health school were selected as intervention group, and 233 students of medical school were selected as control group. The food wastage was weighed in both “Sabz” and “Medical” restaurants for a week. Based on training needs of the samples, teaching methods and programs were implemented in the intervention group for a month. The clients of both restaurants were followed 4 weeks after the intervention. The food waste was weighed after 4 weeks. Data were analyzed using SPSS software version 16 and statistical tests (Wilcoxon, Chi-squared, McNemar, and Mann–Whitney tests). RESULTS: The results obtained from Wilcoxon test showed that, the means of awareness, attitude, and behavior were significantly improved after the intervention in the intervention and control groups (P < 0.001). After the intervention, according to the number of served foods, it was expected that the weight of food wastage to be 341.37 kg/week, but this figure was reduced to 224.98 kg/week after the intervention. CONCLUSIONS: This study has confirmed the effectiveness of implementation of interventions on enhancement of knowledge, attitude, and behavior of people about consumption of food and amount of wastage. The authors suggest that to investigate sustainability of effect of intervention on behavior of food consumption and wastage production, this study could be implemented in different and longer time intervals after the end of project.